Analysis of the variable sites and phylogenetic studies of complete mitochondrial DNA based on the Siniperca scherzeri (Perciformes: Sinipercidae) from four different areas. (June 2013) - Chu, Wuying; Chen, Dunxue; Wang, Kaizhuo; Li, Yulong; Du, Shaojun; Zhang, Jianshe
<x xml:space="preserve">Abstract</x> In this study, we cloned and sequenced the complete mitochondrial DNAs of Chinese mandarin fish, Siniperca scherzeri populations from four different areas of the Yangtze River and the Pearl River systems in China. In the Yangtze River system, fish samples were taken from three regions, Dongting Lake (DT), Poyang Lake (PL) and Xiangjiang River (XR). In the Pearl River system, fish samples were collected from the Lijiang River (LR). The sizes of their complete mitochondrial genome were 16, 502 bp (LR), 16, 508 bp (PL), 16, 502 bp (XR) and 16, 508 bp (DT), respectively. The organization of the S. scherzeri mitochondrial genomes was similar to those reported from other fish mitochondrial genomes. Phylogenetic analyses using N–J computational algorithms showed that the Sinipercidaes are monophyletic and can be divided into two genera, Siniperca and Coreoperca. The S. scherzeri could be divided into two groups along the Yangtze River system and the Pearl River.